2010
DOI: 10.1007/s12029-010-9222-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus-Associated Hepatocellular Carcinoma from India: Role of Viral Genotype and Mutations in CTNNB1 (Beta-Catenin) and TP53 Genes

Abstract: HBV genotype can be ascertained from FFPE sections by sequencing multiple overlapping fragments to avoid the limitation of fragmented DNA. Genotype D was the common genotype in HBV-associated HCC. The very low frequency of TP53 mutation suggests low levels of aflatoxin B₁ exposure. The beta-catenin pathway appears not to be significantly involved in HBV-related HCC in India. However, further larger studies are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…EpCAM is one of the markers that identify CSCs within a tumour 19 20 . Signaling pathways in HCC in Indian patients may be different from those in the West 21 22 , underscoring the importance of re-examining the biological correlates of CSC and HCC in this population.…”
Section: Discussionmentioning
confidence: 99%
“…EpCAM is one of the markers that identify CSCs within a tumour 19 20 . Signaling pathways in HCC in Indian patients may be different from those in the West 21 22 , underscoring the importance of re-examining the biological correlates of CSC and HCC in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The very low frequency of TP53 mutation suggests low levels of Aflatoxin B1 exposure. 40 Because of the discrepant and isolated reports on genetic risk factors for HCC it can be concluded that currently data is insufficient to implicate any genetic risk factor for HCC in India. Table 1 shows among the HCC patients without cirrhosis, 63.46% were positive for HBV markers, 1.92% for HCV markers and none had markers for both.…”
Section: Are Indians Genetically More Prone To Hepatocellular Carcinoma?mentioning
confidence: 99%
“…We did not find nuclear staining for beta catenin in tumor cells of both HCC and FLC in the present case. Our previous study [ 12 ] has also shown that the beta-catenin pathway appears to be infrequent in hepatitis B related HCC in India.…”
Section: Discussionmentioning
confidence: 99%